Digital Cloud: Representasi Transparansi Keberagamaan di Facebook - Nawawi, Imam (FIKRAH, 2018)
Digital Clouds is a communication medium that connects every internet user. Clouds in every variety of forms as a facilitator of individual freedom. This paper is used to express the forms of transparency that are on Facebook social media. With qualitative and qualitative sampling methods, this study examines the digital footprint of Facebook friends in the 2018 political year related to the issue of the Ministry of Religion's 200 Muballigh releases. This study found that the behavior of religious communities in the Facebook era was very central, and had a very close relationship with the development of the present socio-political context. The importance of this study is to present the forms of religious behavior that are widely spread in the social media space such as Facebook.